2017
DOI: 10.3389/fncel.2017.00330
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of PDK1 in the Forebrain Causes Neuron Loss and Increased Apoptosis during Cortical Development

Abstract: Decreased expression but increased activity of PDK1 has been observed in neurodegenerative disease. To study in vivo function of PDK1 in neuron survival during cortical development, we generate forebrain-specific PDK1 conditional knockout (cKO) mice. We demonstrate that PDK1 cKO mice display striking neuron loss and increased apoptosis. We report that PDK1 cKO mice exhibit deficits on several behavioral tasks. Moreover, PDK1 cKO mice show decreased activities for Akt and mTOR. These results highlight an essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Previous studies have demonstrated that the phosphorylation of AKT at Thr308 by PDK1 is essential for its activation [64,65]. Loss of Pdk1 results in decreased AKT activity, consequently leading to an increased apoptosis of excitatory neurons at postnatal rather than embryonic stages [30]. Here, we first examined total AKT level in the ventral telencephalon and observed no significant differences at E16.5 ( Fig.…”
Section: Decreased Activity Of Akt-gsk3β Signaling Pathway After Pdk1mentioning
confidence: 73%
See 3 more Smart Citations
“…Previous studies have demonstrated that the phosphorylation of AKT at Thr308 by PDK1 is essential for its activation [64,65]. Loss of Pdk1 results in decreased AKT activity, consequently leading to an increased apoptosis of excitatory neurons at postnatal rather than embryonic stages [30]. Here, we first examined total AKT level in the ventral telencephalon and observed no significant differences at E16.5 ( Fig.…”
Section: Decreased Activity Of Akt-gsk3β Signaling Pathway After Pdk1mentioning
confidence: 73%
“…Here considering the Dlx5/6-Cre is a powerful tool to delete genes in SVZ progenitors in the ventral telencephalon [14], and the Pdk1 fl/fl line has been employed to disrupt Pdk1 in several studies [30][31][32], combined with the result of Quantitative real-time PCR, Pdk1 could be considered to be efficiently deleted. Most Pdk1 cKO mice died shortly after birth, with a very small number surviving to P15.…”
Section: Loss Of Pdk1 Results In a Severe Reduction In Cortical Intermentioning
confidence: 99%
See 2 more Smart Citations
“…Western blotting was conducted using a protocol described previously [ 3 , 33 ]. Normalized volumes of samples (40 μg total protein) were resolved in 10% 15-well SDS-PAGE gels (invitrogen), transferred to nitrocellulose membrane.…”
Section: Methodsmentioning
confidence: 99%